Gymulation registration systems - Ólafur Andri Ragnarsson (2004)
Verkefnið er opið nemendum og starfsfólki Háskólans á Akureyri This dissertation describes a work of a project to write a database system for the gymnasium Bjarg Akureyri. This software will store all data of the customer’s info and an attendance to the gym. It will also allow the user to watch his weight and measures to allow them to see how there process of changing there live style is going.